Video ethics in educational research involving children: Literature review and critical discussion. Issue 9 (29th July 2021) - Peters, Michael A.; White, E. Jayne; Besley, Tina; Locke, Kirsten; Redder, Bridgette; Novak, Rene; Gibbons, Andrew; O'Neill, John; Tesar, Marek; Sturm, Sean
Abstract: Video ethics in educational research involving children is a recent topic that has arisen since the increase in the use of visual mediums in research (such as photovoice and video) especially with the development of new and ubiquitous internet technologies and social media. This paper emerged as an expressed concerned by a group of scholars associated with the new Video Journal of Education and Pedagogy (Brill) that was established in 2016. The paper is the result of a collective writing process over a period of a few months that discusses visual studies in education and visual ethics in relation to qualitative research in education, and as it applies to children. The article also uses the newly established convention of open review, publishing the results with the paper.